2020
DOI: 10.1097/pr9.0000000000000850
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of exercise-induced analgesia: what we can learn from physically active animals

Abstract: Physical activity produces analgesia through supraspinal, spinal, and peripheral mechanisms. Currently, no exercise mode has proven to be superior to others for analgesic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 164 publications
2
59
0
Order By: Relevance
“…Studies have shown that acute bouts of exercise to muscular fatigue induces nociceptive activity (Taylor et al, 2000), which in turn may trigger the activation of endogenous descending inhibitory and facilitatory pathways from the brain (Villanueva et al, 1996). However, it is unclear whether longer term (3 months) exposure to fatiguing muscle contractions and contractions to volitional muscle failure, as per the protocol in the current strength training group, triggers these same endogenous pathways and/or if these or other pathways are activated differently compared to other exercise modes (Lesnak & Sluka, 2020). This also means that we are unable to recognize which specific pathways that may account for the greater effects on pain sensitization from additional strength training.…”
Section: Comparison Of Effects Across Exercise Modessmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that acute bouts of exercise to muscular fatigue induces nociceptive activity (Taylor et al, 2000), which in turn may trigger the activation of endogenous descending inhibitory and facilitatory pathways from the brain (Villanueva et al, 1996). However, it is unclear whether longer term (3 months) exposure to fatiguing muscle contractions and contractions to volitional muscle failure, as per the protocol in the current strength training group, triggers these same endogenous pathways and/or if these or other pathways are activated differently compared to other exercise modes (Lesnak & Sluka, 2020). This also means that we are unable to recognize which specific pathways that may account for the greater effects on pain sensitization from additional strength training.…”
Section: Comparison Of Effects Across Exercise Modessmentioning
confidence: 96%
“…Several mechanisms may cause the pain-relieving effects of exercise, such as central gating mechanisms (i.e. opioidergic, serotonergic, noradrenergic, and adrenergic pathways (Da Silva Santos & Galdino, 2018)), neuroimmune mechanisms (regulation of pro-inflammatory and anti-inflammatory cytokines (Leung et al, 2016)) and peripheral mechanisms (regulation of adipokines in plasma and cell proliferation and increased cell density locally at sites with tissue damage (Luan et al, 2015;Sun et al, 2019)) (Lesnak & Sluka, 2020). Currently, it is unclear how different exercise modes may modulate pain in KOA differently due to a lack of high-quality randomized controlled trials investigating the longer term (3 months) pain relieving effects of different exercise modes.…”
Section: Introductionmentioning
confidence: 99%
“…We focused our ligand-receptor interaction on muscle to sensory neuron communication because of the link between exercise and pain. A consistent observation in clinical and preclinical pain studies is that exercise is one of the most successful interventions for chronic pain (Sluka et al, 2018;Lesnak and Sluka, 2020;Merkle et al, 2020). One potential explanation for this effect is the production of myokines from exercise that act on sensory neurons to decrease their excitability (Sharma et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…However, exercise also induces analgesic effects (exercise induced hyperalgesia [EIH]) 17 and harnessing these effects could be beneficial for people with pain. The articles by Vaegter and Jones 21 and Lesnack and Sluka 10 comprehensively review the mechanisms of EIH in both clinical populations and animals, respectively. The review by Vaegter and Jones 21 demonstrates that although EIH responses are robust in pain-free individuals, they are more inconsistent in people with musculoskeletal pain, with the opposite effect of hyperalgesia with exercise often occurring.…”
mentioning
confidence: 99%
“…Nevertheless, EIH can be induced in patients with pain by exercising nonpainful body parts and that expectations, preferences, and beliefs can influence hypoalgesic responses and these should be assessed in determining a specific exercise intervention for individual patients. Of course, a more in-depth understanding of the effects of exercise can be gained from animal studies, where Lesnack and Sluka 10 eloquently describe the peripheral and central mechanisms of EIH. Interestingly, they note a U-shaped curve to exercise intensity where exercise of too low or too high an intensity may have detrimental effects, suggesting that there is a sweet spot for exercise prescription that may vary between individuals.…”
mentioning
confidence: 99%